The New Product Line Strategies in Maintaining the Sustainability of SMEs - Rodhiah, Rodhiah; Clarissa, Tara; Valentina, Valentina (CV. Proaksara Global Transeduka, 2024)
The role of product lines is very important in increasing the growth of SMEs. Through a variety of product lines sold, the problem of existing market saturation can be resolved, the emergence of new product lines can expand existing products. PKM activities aim to help MSMEs understand new product line strategies in running a business and maintaining survival in the future. The activity is engaged in a culinary business, with the Pempek Lita located in Jambi that provides various kinds of pempek. In its activities, it faces various problems, especially in carrying out product line strategies, this is due to the lack of knowledge about things related to product lines. For this reason, PKM programmes aim to help improve the business partners' knowledge. The method offered in this activity is online training/socialisation through Zoom meetings. The material to be delivered includes: basic introduction to product lines; product line strategies and others. The results of the activity show that the problems that arise in partner businesses will be resolved, partners can understand the importance of product line strategies for business sustainability.